Syncope in hypertrophic cardiomyopathy. Issue 2 (February 1982) - McKenna, W; Harris, L; Deanfield, J
Abstract : A patient with hypertrophic cardiomyopathy, syncope, and frequent ventricular tachycardia was monitored during a syncopal episode. An unrecordable blood pressure and the loss of a left ventricular outflow tract murmur without evidence of arrhythmia suggested a primary haemodynamic mechanism such as reduction in left ventricular volume.